THERMODYNAMICS AND BIOGEOCHEMISTRY OF LANTHANIDES AND ACTINIDES - Marakushev A.A.; Gavrilov N.M.; Marakushev S.A. (My University, 2004)
The heat capacity (C0p298 ) and entropy (S0298) of elementary substances that occur in a solid, liquid, or gaseous state under standard conditions (T = 298 K and P = 1 atm) are the only thermodynamic properties of chemical elements that are taken into consideration irrespective of their compounds. We used their specific values (J g-1 K-1) and constructed a diagram characterizing the periodicity of their variations as a function of even and odd ordinal numbers of elements. The periodicity of specific heat capacity in the diagram is determined by maximum values corresponding to the alkali metals and minimum values corresponding to the noble gases and gaseous halogens (F and Cl.) Between these extremes, the heat capacity of elements monotonously diminishes with increasing ordinal numbers. The maximums of entropy fall on the noble gases, while deep entropy minimums divide the chemical elements located in ordinal number ranges between noble gases into light (low heat capacity) and heavy (higher heat capacity) groups. This universal subdivision is fundamental and determines a difference of chemical elements, not only in thermodynamic, but also in metallogenic, biogeochemical, and physical properties. This aspect is considered for different periods of the chemical element system.